Selection for Growth Traits on M1V1 Generation of Raja Bulu Banana (Musa paradisiaca Linn.) Obtained by Gamma Rays Irradiation - Nandariyah Nandariyah; Endang Yuniastuti; Sukaya Sukaya; Sonia Ika Yudhita (Universitas Sebelas Maret, 2021)
Raja Bulu is one of the banana varieties favored by the community because of its thick fruit flesh and sweet taste. However, its parthenocarpic characteristic and vegetative propagation make this banana variety has limited genetic variation. Attempt to improve the genetic variation was conducted through induced mutation breeding using gamma-ray mutagens. This research aimed to select M1V1 generation of Raja Bulu banana (Musa paradisiaca Linn.) obtained by gamma rays’ irradiation for their growth traits which are expected to produce banana varieties that have an early maturity and high yield. This study used a randomized complete block design without replication by observing the generative growth of each individual of Raja Bulu banana irradiated by gamma rays and without radiation as a control. The results showed that gamma-ray irradiation treatment caused Raja Bulu banana to be harvested earlier and produced higher fruit weight than controls. The gamma-ray irradiation had a random influence on Raja Bulu bananas. The 10 Gy gamma-ray irradiation dosage influenced the morphological diversity in the generative phase of Raja Bulu banana. The treatment of gamma irradiation resulted in 5 individual plants that flowered and matured earlier as compared to controls.